The unworthy : a novel - Bazterrica, Agustina María, 1974- (Scribner, an imprint of Simon & Schuster, 2025)
"From her cell in a mysterious convent, a woman writes the story of her life in whatever she can find--discarded ink, dirt, and even her own blood. A lower member of the Sacred Sisterhood, deemed an unworthy, she dreams of ascending to the ranks of the Enlightened at the center of the convent and of pleasing the foreboding Superior Sister. Outside, the world is plagued by catastrophe--cities are submerged underwater, electricity and the internet are nonexistent, and bands of survivors fight and forage in a cruel, barren landscape. Inside, the narrator is controlled, punished, but safe. But when a stranger makes her way past the convent walls, joining the ranks of the unworthy, she forces the narrator to consider her long-buried past--and what she may be overlooking about the Enlightened. As the two women grow closer, the narrator is increasingly haunted by questions about her own past, the environmental future, and her present life inside the convent. How did she get to the Sacred Sisterhood? Why can't she remember her life before? And what really happens when a woman is chosen as one of the Enlightened?" --